Evaluation of RIPASA and ALVARADO Score for Diagnosis of Acute Appendicitis - Sania Sabir , Shahroz Saud Ahmed , Maria Zafar (Journal of Rawalpindi Medical College, 2018)
Background:To evaluate RIPASA and ALVARADO scores for the diagnosis of acute appendicitis. Methods : In this cross sectional study, patients presenting with features suggestive of acute appendicitis and who had undergone appendectomy, were included. All those patients whose follow up was not possible with histopathology reports were excluded .Sampling technique was non probability random sampling technique.Frequencies , percentages were calculated for categorical variables i.e. different parameters of RIPASA and ALVARDO scoring system. Sensitivity and specificity of both scoring system was checked keeping histopathology reports as gold standard . Results :Mean age was 20.2 years. Minimum RIPASA score was 5.5 , maximum 14 ,mean 10.64 and range turned out to be 8.50 with standard deviation of 1.639. P value for RIPASA score was 0.015 . 155 cases had RIPASA score of 7.5 and above . Maximum ALVARADO score was 9 and minimum 2 , mean of 8.13 and standard deviation of 1.48. Majority (92.5%) had ALVARADO score more than 5 . P value for ALVARADO score was 0.001 .The gold standard for diagnosing acute appendicitis was histopathology report which was positive in 90.6%.Sensitivity of RIPASA score 95 % ALVARADO 88 % .Specificity of RIPASA was 21 % while of ALARADO 42 %. Conclusion: RIPASA score >7 and ALVARADO > 6 are significant for diagnosing appendicitis .RIPASA is more sensitive but less specific than ALVARADO score for diagnosing acute appendicitis.